Geographical characteristics of contemporary international migration in and into Europe - Kocsis, Károly; Molnár SansumJudit; Kreinin, Lea; Michalkó, Gábor; Bottlik, Zsolt; Szabó, Balázs; Balizs, Dániel; Varga, György (Hungarian Geographical Bulletin, 2017)
The study offers a short geographical overview of migration studies and theories, doing so in the context of the European migration crisis of 2015–2016. It outlines the history of international migrations affecting Europe (immigration, emigration, migration within Europe and between countries) and the demographic effects of such migration on the present European population. It then analyses and examines the global and regional causes of recent migration to Europe (the European Economic Area, EEA), the countries of origin of the migrants, the main routes of migration, and the destination areas in Europe. As far as intercontinental migration is concerned, Europe was characterised by emigration between the 16th and mid-20th centuries (partly in consequence of colonisation) and mainly by immigration thereafter. Immigration has principally affected Western Europe, the more developed part of the continent. In consequence of post-World War II reconstruction, dynamic economic development, local labour shortages, and the decolonisation process, Western Europe received many migrants, initially from the Mediterranean region and subsequently (i.e. after the collapse of communism in 1989–1990) from the post communist European countries. Meanwhile, the core areas of the EEA became the main destination for migrants coming from predominantly Muslim regions in Asia and Africa (SW Asia, Muslim Africa). This decades-old process has recently accelerated and now constitutes mass migration. The global and regional causes of such intercontinental migration in the sending areas are as follows: the population boom, economic backwardness, unemployment, growing poverty, climate change, desertification, negative ecological changes, global political rivalries and local power changes (e.g. the Arab Spring, 2011), growing political instability, wartime destruction, multiple and cumulative crises, general hopelessness and despair.